1960
DOI: 10.1111/j.1423-0410.1960.tb04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies of the I Antigen and Antibody

Abstract: Summary The blood of a Puerto Rican, of a West Indian Negress and of several members of a Baltimore Negro family is described. The red cells of these people are apparently of the phenotype i and their serum contains anti‐I. The samples differ somewhat from that of the English i donor of Jenkins et al. (1960): their red cells are not quite so weak in I antigen and the anti‐I in their serum is more restricted in range. The anti‐I in the serum of the Puerto Rican is outstanding because it contains what may be cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 5 publications
0
73
0
Order By: Relevance
“…This finding, as well as the preferential agglutination by some samples of anti-I associated with ABO group (18), suggests that I, and probably i, antigenic determinants may contain sugar units resembling those of the ABO system. In addition, the recent studies of Schmidt, Barile, and McGinniss (19) indicate that red cell I activity, as measured by selected specimens of anti-I, may be greatly decreased in leukemia, a phenomenon that resembles the loss of A antigen in this disease.…”
Section: Tests With Other Antibodiesmentioning
confidence: 71%
“…This finding, as well as the preferential agglutination by some samples of anti-I associated with ABO group (18), suggests that I, and probably i, antigenic determinants may contain sugar units resembling those of the ABO system. In addition, the recent studies of Schmidt, Barile, and McGinniss (19) indicate that red cell I activity, as measured by selected specimens of anti-I, may be greatly decreased in leukemia, a phenomenon that resembles the loss of A antigen in this disease.…”
Section: Tests With Other Antibodiesmentioning
confidence: 71%
“…The heterogeneity of anti-1 sera is well known [2,3,5]. It was surprising then to find that macroglycolipids react with all 31 anti-I sera tested so far.…”
Section: Resultsmentioning
confidence: 99%
“…191 described an I-active glycoprotein. I-active material was found in hydatid cyst fluid [3], in saliva [12], in amniotic fluid [I31 and human milk [14]. The work carried out in Kabat's laboratory on I-active glycoproteins revealed the extreme complexity of the system claimed the existence of several different I antigens.…”
mentioning
confidence: 99%
“…Later studies found that cord blood cells contained a very weak I antigen. 2,3 In 1960, Marsh and Jenkins 4 described the first cold agglutinating antibody, named anti-i, which behaved in an opposite manner to anti-I-reacting strongly with cord blood cells and RBCs with the I-negative phenotype but weakly with normal adult RBCs-and thus established the i antigen. 5,6 Expression of the I and i antigens was soon found to have a reciprocal relationship and to be developmentally regulated.…”
Section: Introductionmentioning
confidence: 99%